Prevalence of enamel white spots and risk factors in children up to 36 months old - Tiano, Ana Valéria Pagliari [UNESP] (2009)
The aim of this study was to determine the prevalence of enamel white spots and the quality of oral hygiene in children up to 36 months old, in municipalities with different fluoride levels in the water supply, analyzing the contribution of several variables. After approval of the Ethics Committee, the parents signed an informed consent form and were interviewed about their educational level, economic classification of the family, nursing habits, use of toothpaste, access to dental service and other information. The children were clinically examined using the same codes and criteria established by the WHO (World Health Organization) and ADA (American Dental Association). The data were processed and analyzed with the Epi-info software program, version 3.2, and Microsoft Excel. Fisher's exact test (p<0.05) was applied to assess the association among the variables. The enamel white spot prevalence was 30.8% and the age group, duration of the bedtime milk feeding habit, age of initial practice of oral hygiene and presence of caries lesions with cavitation were considered statistically significant with regard to enamel white spot prevalence (p < 0.05). No association was found between oral hygiene quality and the study variables. © 2009 Sociedade Brasileira de Pesquisa Odontológica.